Effect of deep cryotreated tungsten carbide electrode and SiC powder on EDM performance of AISI 304. (17th November 2019) - Bhaumik, Munmun; Maity, Kalipada
Abstract: Powder mixed electric discharge machining (PMEDM) is a further advancement of conventional EDM process in which electrically conductive powder is suspended in the dielectric fluid to enhance the material removal rate (MRR) along with the surface quality. Cryotreatment is introduced in this process for improving the cutting tool properties as well as tool life. In this investigation, EDM is performed for the machining of AISI 304 stainless steel using cryotreated double tempered tungsten carbide electrode when SiC powder is suspended in the kerosene dielectric. The influence of process parameters viz. pulse on time, peak current, duty cycle, gap voltage and powder concentration on tool wear rate (TWR), surface roughness (Ra ), and MRR has been studied. Metallographic analysis was carried out for the machined surfaces. By the addition of powder concentration and cryotreated double tempered electrode, significant improvement in the machining efficiency has been found out. When cryotreated electrode used MRR, TWR and Ra decreased by 12%, 24% and 13.3%, respectively and when SiC powder used MRR increased by 23.2%, TWR and Ra decreased by about 25% and 14.2%, respectively.